Estimación de la huella hídrica en cultivos de pitahaya (Hylocereus undatus) en CIIDEA ESPAM MFL - Barreiro Moreira, Patricia Soraya (2022)
The objective of the research was to evaluate the green water footprint in pitahaya (Hylocereus undatus) cultivation through a comparative analysis under dry and rainy season conditions in the CIIDEA area of the ESPAM MFL. To meet this objective, the agroproductive environment of the Hylocereus undatus crop was characterized. Subsequently, the green water footprint of the crop in dry and rainy seasons was calculated, and alternatives for optimal water management were proposed. The methods used were the theoretical bibliographic method and the hypothetical deductive method. The applied techniques were the survey and the CropWat 8.0 irrigation software. The results show that the study area has an area of 609.5 m2 in which 80 Hylocereus undatus are planted in a sandy loam soil, with a drip irrigation system that provides water from the Carrizal River that threw an expense in the dry season of 8.26 m3 while in the rainy season it yielded a value of 89.92 m3, later the green water footprint was calculated and a value of 24.58 m3/ton was reflected in the dry season, while, in the rainy season it was 267.62 m3/ton. Therefore, the Hylocereus undatus Crop Irrigation Manual will allow optimal water management, since it will avoid unnecessary water consumption in this type of crop.